2002
DOI: 10.1046/j.1365-2036.2002.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the specific 5HT4 receptor agonist, prucalopride, on colonic motility in healthy volunteers

Abstract: Background: Prucalopride is a selective and specific 5‐hydroxytryptamine4 receptor agonist that is known to increase stool frequency and to accelerate colonic transit. Aim: To investigate the effect of prucalopride on high‐amplitude propagated contractions and segmental pressure waves in healthy volunteers. Methods: After 1 week of dosing (prucalopride or placebo in a double‐blind, randomized, crossover fashion), colonic pressures were recorded in 10 healthy subjects using a solid‐state pressure catheter with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 20 publications
2
54
0
2
Order By: Relevance
“…The observed activity in the colon is comparable to the effects seen following a treatment with other colonic prokinetics such as prucalopride, or other serotonin receptor agonists or neostigmine; however, in contrast to the above mentioned drugs RM-131 exhibits a delayed effect (24-36 hour postadministration) on the colonic motility. [42][43][44] To further characterize the effects reported in the human colon the same group of authors evaluated the clinical efficacy of RM-131 in patients with confirmed CC. Similarly to their first clinical trial, the propulsive effects of RM-131 were confirmed, and the trial added that the duration of RM-131 is long-lasting with RM-131 activity being reported for a minimum of 1 hour.…”
Section: Relamorelinmentioning
confidence: 99%
“…The observed activity in the colon is comparable to the effects seen following a treatment with other colonic prokinetics such as prucalopride, or other serotonin receptor agonists or neostigmine; however, in contrast to the above mentioned drugs RM-131 exhibits a delayed effect (24-36 hour postadministration) on the colonic motility. [42][43][44] To further characterize the effects reported in the human colon the same group of authors evaluated the clinical efficacy of RM-131 in patients with confirmed CC. Similarly to their first clinical trial, the propulsive effects of RM-131 were confirmed, and the trial added that the duration of RM-131 is long-lasting with RM-131 activity being reported for a minimum of 1 hour.…”
Section: Relamorelinmentioning
confidence: 99%
“…For these reasons, its use in clinical practice is very limited. Prucalopride is a highly selective 5-HT4 receptor agonist with strong enterokinetic activity [124,125] and requires lower dose for this therapeutic effect [119] making this drug potentially suitable for bloating patients [126] . Itopride, a dopamine receptors antagonist and acetylcholinesterase inhibitor, has shown conflicting results in patients with functional dyspepsia [127,128] .…”
Section: Treatmentmentioning
confidence: 99%
“…All in all, the available literature and those provided in the study suggest that since relamorelin might be considered as a relatively pure ''pusher,'' at least in the colon, this drug may be effective in the treatment of constipation, even though its propulsive effects seem to be relatively feeble when compared with those characteristic of other drugs [5][6][7][8]. Nevertheless, its ability to stimulate proximal gut motility [11] combined with its subcutaneous route of administration might benefit not only conventional constipated subjects, but also other subtypes of constipation such as in post-operative and neutrally compromised patients, and in patients refractory to all other medications [13].…”
mentioning
confidence: 99%
“…Caution should, however, be the rule when interpretating such data, since some of these studies have been conducted only in healthy volunteers [6][7][8], and at least for one of them the findings have not been reproduced in either controls or patients [9]; therefore, further data, possibly obtained in patients with chronic constipation, would be indeed welcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation